2022
DOI: 10.55519/jamc-03-10181
|View full text |Cite
|
Sign up to set email alerts
|

Surface Microhardness of Microhybrid and Nanocomposite After Storage in Mouth Washes

Abstract: Background: Dental composites are aesthetic direct restorative material. However, the effect of mouthwashes on the durability of the material is controversial. This study evaluated and compared the influence of mouthwash composition on the surface hardness of nanofilled (Z350XT) and microhybrid (P60) resin composites. Methods: Comparative in-vitro study was conducted over 6 months at Multan Medical & Dental College. Sixty-four disc-shape specimens of each {nanofilled (Z350XT) and microhybrid (P60)} resin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…The role of AMH in adult males is not completely understood, but it is believed to correlate with spermatogenesis. As for InhB, AMH may be considered as a marker of Sertoli cell maturation, whereby more immature cells produce more AMH than less immature cells, possibly reflecting the degree of spermatogenesis [21] , [33] , [34] , [35] , [36] . This led to the hypothesis that AMH levels could predict SR at mTESE.…”
Section: Discussionmentioning
confidence: 99%
“…The role of AMH in adult males is not completely understood, but it is believed to correlate with spermatogenesis. As for InhB, AMH may be considered as a marker of Sertoli cell maturation, whereby more immature cells produce more AMH than less immature cells, possibly reflecting the degree of spermatogenesis [21] , [33] , [34] , [35] , [36] . This led to the hypothesis that AMH levels could predict SR at mTESE.…”
Section: Discussionmentioning
confidence: 99%
“…Following many studies, the hardness of some types of the composite was found highly affected by using Listerine mouthwash. This softening effect was found to directly adhere to the alcohol percentage (25,27,28) . On the other hand, in a study by Spuldaro et.…”
mentioning
confidence: 89%
“…Several studies suggested that Listerine as one of the commonly used mouthwashes may adversely affect the hardness of composite resin. This may relate to the high alcohol-content percentage of either ethanol or methanol (12,25) . Material hardness is related directly to its strength and rigidity, and the clinical durability may be implicated due to chemical softening resulting from the use of some mouthwashes (26) .…”
mentioning
confidence: 99%
“…En diversos estudios sobre la microdureza de las resinas compuestas polimerizadas, se hace referencia a que en la cara superior de la resina se encontró mayor microdureza que en la cara inferior, variando según la distancia a la que se coloque la unidad emisora de luz que le permitirá fotopolimerizar (19)(20)(21)(22)(23)(24)(25). Al ser así, las resinas son resistentes a las cargas y a la abrasión, y aumenta sus valores mientras más próxima se encuentre la fuente emisora de luz a la resina, siendo esto positivo (25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Introductionunclassified